2019
DOI: 10.1002/jcp.28526
|View full text |Cite
|
Sign up to set email alerts
|

One functional variant in the 3′‐untranslated region of TLR4 is associated with the elevated risk of ventilator‐associated pneumonia in the patients with chronic obstructive pulmonary disease

Abstract: The aim of this study was to identify the association polymorphism (rs11536889) in the 3′‐untranslated region (3′‐UTR) of Toll‐like receptors 4 (TLR4) and the risk for ventilator‐associated pneumonia (VAP). miRNA database online and luciferase assays were used to validate TLR4 as the target gene of miR‐1236. Enzyme‐linked immunosorbent assay analysis and western blot were used to analyze the level of TLR4 in different genotype groups. In the present study, miR‐1236 was predicted to bind to the rs11536889 G all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…In this study, miR‐1236 selectively targeted the mutated 402C>G locus in the FOXL2 CDS, without affecting WT FOXL2 mRNA expression. Preferential targeting of the mutated “G” allele by miR‐1236 was also reported in recent single‐nucleotide polymorphism (SNP) studies: specific miR‐1236 binding to the G allele over the C allele (rs11536889) in the 3′‐UTR of Toll‐like receptor 4 (Zhao et al , 2019) and specific miR‐1236 targeting of the G allele over the T allele (rs4246215) in the 3′‐UTR of Flap endonuclease 1 (Nanda et al , 2018). Furthermore, our in vivo and in vitro analysis of the phenotypes of miR‐1236 KO cells collectively showed that miR‐1236 acted as an oncomiR in AGCT cells by mainly causing selective variant FOXL2 mRNA degradation (Figs 6 and 7).…”
Section: Discussionmentioning
confidence: 69%
“…In this study, miR‐1236 selectively targeted the mutated 402C>G locus in the FOXL2 CDS, without affecting WT FOXL2 mRNA expression. Preferential targeting of the mutated “G” allele by miR‐1236 was also reported in recent single‐nucleotide polymorphism (SNP) studies: specific miR‐1236 binding to the G allele over the C allele (rs11536889) in the 3′‐UTR of Toll‐like receptor 4 (Zhao et al , 2019) and specific miR‐1236 targeting of the G allele over the T allele (rs4246215) in the 3′‐UTR of Flap endonuclease 1 (Nanda et al , 2018). Furthermore, our in vivo and in vitro analysis of the phenotypes of miR‐1236 KO cells collectively showed that miR‐1236 acted as an oncomiR in AGCT cells by mainly causing selective variant FOXL2 mRNA degradation (Figs 6 and 7).…”
Section: Discussionmentioning
confidence: 69%
“…In this study, miR-1236 selectively targeted the mutated 402C>G locus in the FOXL2 CDS, without affecting WT FOXL2 mRNA expression. Preferential targeting of the mutated 'G' allele by miR-1236 was also reported in recent single-nucleotide polymorphism (SNP) studies: specific miR-1236 binding to the G allele over the C allele (rs11536889) in the 3′-UTR of Toll-like receptor 4 (Zhao, Feng et al, 2019) and specific miR-1236 targeting of the G allele over the T allele (rs4246215) in the 3′-UTR of Flap endonuclease 1 (Nanda, Kumar et al, 2018). Furthermore, our in vivo and in vitro analysis of the phenotypes of miR-1236 KO cells collectively showed that miR-1236 acted as an oncomiR in AGCT cells by causing selective variant FOXL2 mRNA degradation (Fig 6 and 7).…”
Section: Discussionmentioning
confidence: 61%
“…Recent research on VAP risk factors reported some new findings. Six et al [36] suggested that hyperoxemia was a potential risk factor for VAP. Excess oxygen administration can damage tissues through the production of reactive oxygen species (ROS) [53].…”
Section: Discussionmentioning
confidence: 99%
“…The full texts of 69 potentially eligible studies were then strictl y assessed. Sixteen studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] were included in the systematic review. Finally, 12 studies [23][24][25][26][27][28][29][30][31][32][33][34] were included in the present meta-analysis (…”
Section: Literature Selectionmentioning
confidence: 99%